Short-Term Outcomes of a Two-Component Total Ankle Replacement in Revision Arthroplasty - Peter Kvarda MD; Laszlo Toth; Tamar Horn-Lang; Roman Susdorf PhD; Roxa Ruiz MD; Beat Hintermann MD (Foot & Ankle Orthopaedics, 2022)
Category: Ankle Arthritis; Ankle; Hindfoot Introduction/Purpose: Given the growing number of primary total ankle replacements (TAR), an increase in the numbers of failed ankles and consecutive revisions might be expected. Achieving a stable and balanced ankle based on stable components while preserving the remaining bone stock as much as possible, are crucial for success in revision TAR. Most reported techniques rely on bulky implants with extended fixation features. Since 2018, we have used a novel 3-component ankle for revision surgery that is converted in situ to a fixed-bearing 2-component ankle once the components have found their position given by the individual anatomy. The purpose of this study was to determine the short-term results of this novel concept in revision TAR. Methods: This single-center retrospective cohort study included 57 patients (57 ankles, mean age 63+-13 years) treated for failed TAR with the semi-constrained HINTERMANN Series H2 © (H2) implant between February 2018 and February 2020. Survival analysis was performed and potential risk factors using Cox regression, were assessed. Clinical and radiological outcomes were assessed preoperatively and at the last follow-up. Clinical outcomes included pain on a visual analog scale (VAS), the American Orthopaedic Foot & Ankle Society (AOFAS) ankle hindfoot score and patient satisfaction. Radiological outcomes were tibial articular surface angle (TAS), tibiotalar surface angle (TTS), talar tilt angle (TT) in the coronal plane and anteroposterior offset (AP-Offset) ratio in the sagittal plane, as well as signs of radiolucency and/or loosening on plane weightbearing radiographs. Results: The median follow-up was 2 (2.0 to 4.0) years. The cumulative incidence for secondary revision after 1 and 2 years was 5.1% (95%CI 0-11) and 7.4% (0-14) respectively. Four patients needed a secondary revision (three for pain/arthrofibrosis and one for aseptic loosening). While the AOFAS hindfoot score increased from median 54 (range 9-94) to 75 (19-98) (p=0.00001), satisfaction increased from moderate to good (p=0.0017). Radiographically, all components were stable without signs of increased shear-forces in terms of loosening or radiolucency. Conclusion: Obtained results with the novel customized semi-constrained total ankle implant design at short-term are encouraging, with a satisfactory survival rate and acceptable revision rate. The fixation concept without extended fixation features was shown to last against increased shear forces.